Future social research in Ireland - Fogarty, Michael P. (Statistical and Social Inquiry Society of Ireland, 1969)
What are the main priorities for economic and social research in Ireland, looking up to five or ten years ahead ? Within that list of priorities, what ought to be the main tasks of ESRI ? The Institute is intended to have not only academic freedom but an academic standard of work, meaning work of a kind on which staff with the abilities and interests which one would expect to find m a university can be employed without wasting the inabilities and with satisfaction to themselves. Projects must be relevant to Ireland, but subject to this can be weighted more towards direct usefulness or towards the advancement of knowledge in particular disciplines, according to personal interest.
Read before the Society, 17 January 1969
Keywords: Social research; Economic research; Research priorities; Economic and Social Research Institute; 314.15